2020
DOI: 10.18273/revsal.v52n3-2020015
|View full text |Cite
|
Sign up to set email alerts
|

Comportamientos individual y social: Estrategias para mantener acciones preventivas en tiempos de epidemia

Abstract: La modificación de comportamientos, como hacer un hábito el uso del tapabocas, el distanciamiento físico, el lavado de manos y el confinamiento, en una situación de pandemia (como la actual por COVID-19), puede constituirse en un reto para el individuo y la sociedad, así esto pueda representar una ganancia para la propia salud de las personas. Cuando el individuo no se percibe en riesgo frente a una condición de salud, ni identifican la gravedad de la misma, difícilmente generará cambios en sus comportamientos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
1
0
2
Order By: Relevance
“…Results indicated that most phone interactions occur while waiting at red traffic lights, with percentages ranging from 14% (reading emails, the least prevalent) to 38% (voice calling, the most frequently reported task). These findings align with previous observational studies, emphasizing that drivers actively seek low-complexity situations to reduce the risk associated with distraction ( Amaya-Castellanos, 2020 ; Russo et al, 2018 ). Importantly, it remains unclear whether these self-regulatory behaviors have actual implications for safety.…”
Section: Discussionsupporting
confidence: 91%
“…Results indicated that most phone interactions occur while waiting at red traffic lights, with percentages ranging from 14% (reading emails, the least prevalent) to 38% (voice calling, the most frequently reported task). These findings align with previous observational studies, emphasizing that drivers actively seek low-complexity situations to reduce the risk associated with distraction ( Amaya-Castellanos, 2020 ; Russo et al, 2018 ). Importantly, it remains unclear whether these self-regulatory behaviors have actual implications for safety.…”
Section: Discussionsupporting
confidence: 91%
“…Controlling these types of communicable diseases depends mainly on the knowledge, attitudes, practices, and behavior of the population regarding their daily interactions, which underlie socially responsible behavior [58]. One example of this is the use of masks, physical distancing, hand washing, and itinerant confinement [59], setting a real challenge for the individual and society in general. In this scenario, preventive measures can be stimulated with greater force in contexts where comprehensive training has been sought in terms of behavioral awareness, where social responsibility and spiritual intelligence flow [60].…”
Section: Covid-19: Spiritual Intelligence and Social Responsibilitymentioning
confidence: 99%
“…Diversos estudios muestran que las condiciones de distanciamiento social se expresan en la población en estrés, ansiedad, síntomas depresivos, insomnio, negación, ira y temor 38 . Esta situación se ha presentado de manera aguda en la población de Santander, donde se ha reportado desde el inicio de la cuarentena que aumentó cerca de un 40 % los casos de intento de suicidio.…”
Section: Salud Mentalunclassified